The Aplication Of Education Quality Standards In Creating Effective Islamic Religious Schools - Suharyanto, Suharyanto; Handayani, Sri; Amaly, Norsyam; Sulaiman, Sulaiman (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The education quality system is implemented in order to provide confidence and trust to parents of students that the learning process is taking place as expected so that the goals of national education are achieved. Meanwhile, effective schools can be realized if the education quality system is implemented consistently and with high commitment. This study aims to find and describe the application of an education quality system that contributes positively to creating effective schools. This research includes qualitative research with a case study approach. The data in this study are in the form of written data and oral data sourced from academic settings. The sample or study object under study was selected based on purposive sampling. The selected samples from the data are used as examples in this study. From this sample, the researcher described things that can be interpreted according to the research objectives. The number of samples in this study were 24 people. They are teachers with five years of service and above spread over three schools. The findings of the research indicated that an education quality system is needed by parents of students to provide guarantees and certainty related to the learning process in schools. In addition, effective schools are realized because one of the factors is the implementation of a comprehensive education quality system.